The development and commercialization of women’s football - Kalliovaara, Taru (My University, 2024)
This paper examines the commercialization of women's football, tracing its historical development, exploring value creation dynamics, and addressing key challenges. The historical development of women's football is highlighted in order to stress the difficult path the sport and the players have went through fighting societal norms. The paper explores value creation within the women's football industry, emphasizing especially sponsorship marketing's role in revenue generation and visibility. Challenges, such as gender inequality and risks of commercialization, are discussed, with a focus on their implications. Solutions for sustainable commercialization are proposed, emphasizing the sport's unique traits and offering actionable suggestions. The positive traits linked to women’s sport are being accentuated in order to give insightful thought about how the commercialization of women’s football can be developed in the future.

Tässä tutkielmassa tarkastellaan naisten jalkapallon kaupallistumista, seuraten sen historiallista kehitystä, tutkien arvonluontidynamiikkaa sekä käsitellen keskeisiä haasteita. Naisten jalkapallon historiallista kehitystä korostetaan, jotta voidaan painottaa vaikeaa polkua, jonka laji ja pelaajat ovat kulkeneet taistellessaan yhteiskunnallisia normeja vastaan. Tutkielma tutkii arvonluontia naisten jalkapallossa, korostaen etenkin sponsorointimarkkinoinnin roolia tulonhankinnassa ja näkyvyyden luomisessa. Haasteita, kuten sukupuolten välistä epätasa-arvoa ja kaupallistamisen haasteita käsitellään keskittyen niiden vaikutuksiin. Kestävälle kaupallistamiselle esitetään ratkaisuja painottaen lajille ainutlaatuisia ominaisuuksia ja niihin perustuvia ratkaisuja. Naisten urheiluun liitettäviä positiivisia ominaisuuksia nostetaan esiin, tarjotakseen oivaltavia ideoita siitä, miten naisten jalkapallon kaupallisuutta voidaan tulevaisuudessa kehittää.
Keywords: sport commercialization, women’s football, sport sponsorship, sport marketing, gender equality in sport, football commercialization, partnership, women athletes, sport inequality, commercialization of women’s sport